Analisis Peran Industri Hotel Syariah Dalam Mendukung Kota Padang Panjang Sebagai Kota Serambi Mekkah - Ridho Kurniawan (Journal of Tourism Sciences, Technology and Industry, 2025)
This research analyzes the role of sharia hotels in strengthening the brand of Padang Panjang City as the Veranda Of Mecca. Using descriptive qualitative methods, data were collected through observations and in-depth interviews at several sharia hotels. The results show that sharia hotels play a strategic role in building the city's religious identity through the application of sharia principles to services, facilities, operational policies, and hotel ethics. The presence of sharia hotels not only strengthens the city's Islamic image but also impacts the local economy, tourist comfort, and increases public sharia literacy. However, obstacles remain, such as the lack of standard sharia certification and variations in the implementation of standard operating procedures (SOPs) at each hotel. Strategies such as strengthening sharia-based SOPs, collaborating with halal MSMEs, and ethical digital promotion have proven effective in supporting Padang Panjang's brand as the Kota Serambi Mekkah. This study concludes that sharia hotels function as cultural, religious, and economic instruments that strengthen the sustainability of the city's identity based on Islamic values.